Soil micronutrient contents and relation to other soil properties in Ethiopia - Haque, I.; Lupwayi, N.Z.; Tadesse, T. (Informa UK Limited, 2000)
Alfisols, Vertisols, Inceptisols, Aridisols, Mollisols, and Entisols were sampled (0-30 cm) from 32 locations across Ethiopia. The soils were analyzed for copper (Cu), zinc (Zn), manganese (Mn), and iron (Fe) contents using 0.005 M diethylene triamine pentaacetic acid (DTPA), 0.05 M hydrochloric acid (FICl), and 0.02 M ethylene diamine tetraacetic acid (EDTA) extractants. EDTA extracted more of each micronutrient than DTPA, which extracted greater amounts than HC1. The quantities of EDTA and DTPA extractable micronutricnts were significantly correlated, and were in the order: Mn>Fe>Cu>Zn. The order of HCI-extractable micronutrients was Mn>Fe>Zn>Cu. Micronutrient contents of Mollisols, Vertisols, and Alfisols were usually greater than those of the other soils, and Entisols usually had the lowest micronutrient contents. The contents were mostly positively correlated with clay and Fe 203 contents, but negatively correlated with soil pH and Al 203 contents. While comparison of DTPA-and EDTA-extractable micronutrients with critical levels showed that most soils had adequate amounts of the micronutrients for crops, the amounts extracted by HIC were below critical levels in most soils. Since the critical levels that were used in the comparisons were not established in Ethiopia, calibration of the soil contents of these micronutrients with crops grown in Ethiopia is required to identify the most suitable extractant(s).